Federated Search in Libraries: An Overview in Academic Libraries - Dwi Fajar Saputra; Zayyin Abdul Quddus; Putra Pertama Budianto; Bintang Mahaputra Nararya Rabbani (Pusat Publikasi Ilmiah UIN Fatmawati Sukarno Bengkulu, 2024)
One essential piece of technology that simplifies the process of finding information across a variety of databases and sources in academic libraries is federated search systems. By using a single query interface, these systems, also known as meta-search engines, allow users to simultaneously search through a variety of resources, such as databases, books, and electronic journals. By combining results from several publishers and platforms into a single format, this feature greatly improves the efficacy and efficiency of academic research while also saving time and streamlining user interactions. An overview of federated search technology is given in this study, with particular attention on how it might be integrated into academic libraries. It talks about how these systems have developed, the technological difficulties they provide, and the advantages they have for educational institutions. The research also looks at case studies from different university libraries to showcase effective implementations. It also discusses the possibility for federated search systems in the future, including the incorporation of machine learning and artificial intelligence to enhance and customize search results. The purpose of this overview is to highlight the value of federated search engines in improving the usability and accessibility of scholarly materials, therefore assisting academic institutions in their larger endeavors to promote research and learning.